Unraveling survival disparities in primary central nervous system (CNS) lymphoma: an analysis of race, socioeconomic factors, and treatment outcomes using the surveillance, epidemiology, and end results program (2000–2021) - Shahzaib Maqbool; Mohammad Ebad Ur Rehman; Ramesha Tahir; Hafsa Arshad Azam Raja; Mouzma Ali; Muhammad Ibrahim; Jacob Guerrero; Abdur Rehman; Imran Khan; Abat Khan; Jose D. Sandoval-Sus (Cancer Causes & Control, 2026)

Parity and breastfeeding are contributing factors for geographical differences in breast cancer risk - Boon Hong Ang; Shivaani Mariapun; Farahida Mohd Farid; Imelda Suhanti Ishak; Muhammad Faiz Md Taib; Asfarina Ab Rahim; Lenjai Anak Jembai; Tania Islam; Kartini Rahmat; Farhana Fadzli; Nur Aishah Mohd Taib; Cheng Har Yip; et al. (Cancer Causes & Control, 2025)

Air quality and cancer risk in the All of Us Research Program - Andrew Craver; Jiajun Luo; Muhammad G. Kibriya; Nina Randorf; Kendall Bahl; Elizabeth Connellan; Johnny Powell; Paul Zakin; Rena R. Jones; Maria Argos; Joyce Ho; Karen Kim; et al. (Cancer Causes & Control, 2024)
Introduction The NIH All of Us Research Program has enrolled over 544,000 participants across the US with unprecedented racial/ethnic diversity, offering opportunities to investigate myriad exposures and diseases. This paper aims to investigate the association between PM 2.5 exposure and cancer risks. Materials and methods This work was performed on data from 409,876 All of Us Research Program participants using the All of Us Researcher Workbench. Cancer case ascertainment was performed using data from electronic health records and the self-reported Personal Medical History questionnaire. PM 2.5 exposure was retrieved from NASA’s Earth Observing System Data and Information Center and assigned using participants’ 3-digit zip code prefixes. Multivariate logistic regression was used to estimate the odds ratio (OR) and 95% confidence interval (CI). Generalized additive models (GAMs) were used to investigate non-linear relationships. Results A total of 33,387 participants and 46,176 prevalent cancer cases were ascertained from participant EHR data, while 20,297 cases were ascertained from self-reported survey data from 18,133 participants; 9,502 cancer cases were captured in both the EHR and survey data. Average PM 2.5 level from 2007 to 2016 was 8.90 μg/m 3 (min 2.56, max 15.05). In analysis of cancer cases from EHR, an increased odds for breast cancer (OR 1.17, 95% CI 1.09–1.25), endometrial cancer (OR 1.33, 95% CI 1.09–1.62) and ovarian cancer (OR 1.20, 95% CI 1.01–1.42) in the 4th quartile of exposure compared to the 1st. In GAM, higher PM 2.5 concentration was associated with increased odds for blood cancer, bone cancer, brain cancer, breast cancer, colon and rectum cancer, endocrine system cancer, lung cancer, pancreatic cancer, prostate cancer, and thyroid cancer. Conclusions We found evidence of an association of PM 2.5 with breast, ovarian, and endometrial cancers. There is little to no prior evidence in the literature on the impact of PM 2.5 on risk of these cancers, warranting further investigation.

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)